Financial Accounting and Investment Management - DE BONDT, WERNER; MONAHAN, STEVEN J. (The Accounting Review, 2010)
• Accountants and analysts as financial intermediaries Volume I, Part I • Measuring corporate earnings and profitability Volume I, Part II • Financial ratios, the risk of failure, and stock returns Volume I, Part III • Equity valuation Volume I, Part IV • Price-earnings ratios, market-to-book ratios, and stock returns Volume II, Part I • Earnings and stock returns Volume II, Part II • Fundamental analysis and stock returns Volume II, Part III